Role of sulphide reduction by magnesium hydroxide on the sediment of the eutrophic closed bay - Dong Xia (2018)
© 2017 John Wiley & Sons Ltd This study was focused on the effect of magnesium hydroxide (Mg(OH)2) for improving the sediment of aquaculture field and eutrophic closed estuaries. Sediment samples were collected from Omura Bay, Nagasaki, Japan. The change in pH, acid volatile sulphides (AVS) and dissolved organic carbon (DOC) in interstitial water of the sediment samples were measured before and after 20-day incubation under the condition of overlapping seawater at 25°C with 0.3–0.4 mg/L of dissolved oxygen (DO). Hydrogen sulphide (H2S) and the dsrA gene copy number of Grp3 sulphate-reducing bacteria (SRB) in the sediment samples were also measured at 7-day incubation under the same condition. The pH of Mg(OH)2treatment group was significantly increased from 7.43 to 8.25; it was higher compared to the control group which pH was maintained around 7.6. Meanwhile, the AVS content of Mg(OH)2treatment group was significantly reduced and the value was lower than the control group after the 20-day incubation. Each concentration of interstitial water DOC in the treatment group and the control group increased after the incubation from initial value of 15.4–40.1 and 29.0 mg/L respectively. Furthermore, simultaneous decrease in H2S and the dsrA gene copy number of Grp3 SRB was observed at the end of the 7-day incubation by adding Mg(OH)2. It is concluded that the loss of activity of SRB was strongly related to the decrease in sulphide (H2S and AVS) and the increase in DOC was due to the alkalization of the sediment by adding Mg(OH)2.